Pain and tissue damage in response to orthodontic tooth movement: Are they correlated? - Cuoghi, Osmar A. [UNESP]; Topolski, Francielle [UNESP]; de Faria, Lorraine P. [UNESP]; de Mendonça, Marcos R. [UNESP] (Jaypee Brothers Medical Publishing, 2016)
Aim: To evaluate the correlation between pain and tissue damage in response to orthodontic tooth movement (OTM), such as hyalinization and external apical root resorption (EARR). Materials and methods: The literature review was used as a methodological strategy, following the knowledge development process - constructivist (ProKnow-C). Study axes were defined and keywords that best represented each axis were selected. The terms were submitted to an adherence test and validation, resulting in 12 keyword combinations. Searches were carried out in the most representative databases for the selected terms, without restriction as for language or publication dates. Retrieved studies were filtered using the EndNote X6 program and classified according to analysis of title, abstract, and keywords. The final portfolio of articles was submitted to bibliometric and systematic analysis. Results: A total of 1,091 studies were retrieved, out of which 719 were repeated and 335 were removed in the classification stage. A total of 37 articles remained in the final portfolio. Only one article was in line with the purpose of this study, indicating absence of correlation between pain and EARR in response to OTM. Conclusion: Further studies are necessary to confirm whether orthodontic pain might serve as a criterion for the use of appropriate mechanical forces, contributing to minimize tissue damage following OTM. Clinical significance: This article presents a systematic literature review, in which scientific evidence of the correlation between pain and tissue damage during orthodontic movement was studied, providing a scientific answer for the following question: Is pain reported by patients associated with application of inappropriate orthodontic force? Thus, it aims at aiding the orthodontist in the definition of clinical parameters for the use of optimal orthodontic force.
Keywords: Hyalinization; Pain; Root resorption